SOSIALISASI TIPS DAN TRIK PENERAPAN DIGITAL MARKETING PADA SEBUAH PRODUK USAHA DI RPTRA KOMANDO CERIA, KELURAHAN GALUR, JAKARTA PUSAT - Ana Chaerunisyah; Iin Andaryati; Sri Susanti Widyasari; Achmad Barlian; Muh.Ali Maskur (Gapenas Publisher, 2023)
In the modern era, the presence of marketing innovations through digital media such as online stores and social media is crucial for local entrepreneurs, especially the PKK mothers and residents of Galur Subdistrict, Central Jakarta. However, many of them still lack a deep understanding of how to effectively utilize digital media to market their products. Through a community service activity titled